The Timing of Metamorphism, Magmatism, and Cooling in the Zanskar, Garhwal, and Nepal Himalaya - Searle, M. P. (Journal of Nepal Geological Society, 1995)
Following India-Asia collision, which is estimated at ca. 54-50 Ma in the Ladakh-southern Tibet area, crustal thickening and timing of peak metamorphism may have been diachronous both along the Himalaya (pre-40 Ma north Pakistan; pre-31 Ma Zanskar; pre-20 Ma east Kashmir, west Garhwal; 11-4 Ma Nanga Parbat) and cross the strike of the High Himalaya, propagating S (in Zanskar SW) with time. Thrusting along the base of the High Himalayan slab (Main Central Thrust active 21-19 Ma) was synchronous with N-S (in Zanskar NE-SW) extension along the top of the slab (South Tibet Detachment Zone). Kyanite and sillimanite gneisses in the footwall formed at pressure of 8-10 kbars and depths of burial of 28-35 km, 30- 21 Ma ago, whereas anchimetamorphic sediments along the hanging wall have never been buried below ca. 5-6 km. Peak temperatures may have reached 750 on the prograde part of the P-T path. Thermobarometers can be used to constrain depths of burial assuming a continental geothermal gradient of 28-30 °C/km and a lithostatic gradient of around 3.5-3.7 km/kbar (or 0.285 kbars/km). Timing of peak metamorphism cannot yet be constrained accurately. However, we can infer cooling histories derived from thermochronometers using radiogenic isotopic systems, and thereby exhumation rates. This paper reviews all the reliable geochronological data and infers cooling histories for the Himalayan zone in Zanskar, Garhwal, and Nepal. Exhumation rates have been far greater in the High Himalayan Zone (1.4-2.1 mm/year) and southern Karakoram (1.2-1.6 mm/year) than along the zone of collision (Indus suture) or along the north Indian plate margin. The High Himalayan leucogranites span 26-14 Ma in the central Himalaya, and anatexis occurred at 21-19 Ma in Zanskar, approximately 30 Ma after the collision. The cooling histories show that significant crustal thickening, widespread metamorphism, erosion and exhumation (and therefore, possibly significant topographic elevation) occurred during the early Miocene along the central and eastern Himalaya, before the strengthening of the Indian monsoon at ca. 8 Ma, before the major change in climate and vegetation, and before the onset of E-W extension on the Tibetan plateau. Exhumation, therefore, was primarily controlled by active thrusts and normal faults, not by external factors such as climate change.